Thiopental sodium loaded solid lipid nano-particles attenuates obesity-induced cardiac dysfunction and cardiac hypertrophy via inactivation of inflammatory pathway - Canzhan Zhu; Wanjing Li; Xinhong Wang; Jiahong Xue; Ling Zhao; Yafan Song; Tian Zhou; Mingjuan Zhang (Taylor & Francis Group, 2020)
This work evaluates solid lipid nanoparticles of thiopental sodium against obesity-induced cardiac dysfunction and hypertrophy and explores the possible mechanism of action. TS loaded SLNs were formulated by hot-homogenization and solvent diffusion method. TS-SLNs were scrutinized for entrapment efficiency, drug loading capacity, gastric stability, particle size, in vitro drug release. Mice were feed with the normal chow or high-fat diet for 08 weeks to induce obesity and primary cardiomyocytes. The therapeutic effects of thiopental sodium in the high fat diet (HFD) induced cardiac hypertrophy. Systolic blood pressure (SBP) was estimated at a regular time interval. At the end of the experimental study, systolic pressure left ventricular, LV end-diastolic pressure and rate of increase of LV pressure and antioxidant, apoptosis, cytokines and inflammatory scrutinized. HFD induced group mice exhibited a reduction in the body weight and enhancement of cardiac hypertrophy marker and dose-dependent treatment of thiopental sodium up-regulation the body weight and down-regulated the cardiac hypertrophy. Thiopental sodium significantly (p < .001) dose-dependently altered the antioxidant, biochemical, cardiac parameters and remodeling. Thiopental sodium significantly (p < .001) dose-dependently reduced the SBP. Thiopental sodium altered the apoptosis marker, pro-inflammatory cytokines, inflammatory parameters along with reduced the p38-MAPK level. The cardiac protective effect of thiopental sodium shed light on future therapeutic interventions in obesity and related cardiovascular complications via inflammatory pathway.